Exploring an Alternative to the Chilean Textile Waste: A Carbon Footprint Assessment of a Textile Recycling Process - Vasquez-Perez, O; Espinoza-Perez, A; Espinoza-Perez, L (Elsevier B.V., 2022)
Global population growth and rising living standards are increasing apparel consumption. Consequently, the consumption of resources and the generation of textile waste are increasing exponentially. For instance, according to the World Bank, Chile has increased textile imports by 500% in the last 20 years, even though the population has only increased by 26%. This textile import increase has resulted in the clothing desert that has been seen recently in northern Chile because most of the textiles at the end of their useful life will be disposed of in landfills or open dumps. This evidences the urgency of more efficient technologies that reduce the consumption of resources and that value waste on the way to a circular and sustainable economy. Since the textile recycling industry and environmental impact studies are currently in their nascent stages in Chile, the objective of this article is to explore the potential environmental benefits of a textile recycling process and, therefore, the related challenges towards more sustainable options. The considered textile recycling process incorporates mixed waste and is compared with landfills in terms of CO2eq because it represents the conventional treatment of waste and the substitution of products from primary sources. The results show that textile waste landfills emit 423.4 kg CO2eq per ton, while products from primary sources emit an average of 6496.65 kg CO2eq, compared to the textile recycling process that only it emits 1142.12 kg CO2eq per ton, obtaining an average of 5778 kg CO2eq avoided per ton of textile waste, achieving environmental benefits. However, it is necessary to highlight the dependence of this result on the choice of replaced products and the energy matrix. Thus, we assessed the energy matrix, evaluating the positive impact of implementing an energy matrix based on wind or solar energy. © 2022 Elsevier B.V.